Predictive Factors for Lymph Node Metastasis and the Effect on Survival in Early Gastric Cancer Patients with Radical Gastric Resection - Gür, Emine Özlem (Sisli Etfal Hastan Tip Bul, 2019)
OBJECTIVES: Selected patients with early gastric cancer (GC) are treated endoscopically. Lymph node metastasis (LNM) in the T1 stage may also be detected during surgical resection for early GC. The aim of this study was to determine factors associated with LNM and the effect on survival. METHODS: A total of 63 patients with tumor invasion stage T1a or T1b who were operated on for early GC between 2010 and 2018 were included in the study. Parameters were investigated retrospectively to identify predictive factors for LNM and overall survival. Significance was defined with a 2-sided p-value of <0.05. RESULTS: Among the 63 patients, 21 (33.3%) had LNM. Lymphovascular invasion (LVI) (p=0.02) and a high-grade tumor (p=0.02) were significantly associated with LNM. The overall survival rate was 73.0%. The number of patients with LNM was greater among the deceased patients compared with the censored group (p=0.03). The median follow-up time of the entire group was 28 months (range: 12-55 months) while it was 23 months (range: 7-39 months) in the deceased group and 33.5 months (15.5-60 months) in the censored group (p=0.06). The mean survival was 62.36 months in patients with LNM and 71.99 months in those without LNM (p=0.09). The cut-off value determined for the neutrophil-to-lymphocyte ratio (NLR) was 2.33 and it was an effective value in survival analysis (p<0.05). CONCLUSION: Surgical treatment should be considered for early GC patients with high-grade tumors and cases demonstrating LVI. The overall survival was shorter in patients with a high NLR value and LNM.